National Immunization Day: a strategy to monitor health and nutrition indicators - Leonor Maria Pacheco Santos; Rômulo Paes-Sousa; Jarbas Barbosa da Silva Junior; César Gomes Victora
PROBLEM: To achieve the Millennium Development Goals it is necessary to set up low-cost, real-time monitoring systems which can provide feedback to managers and policy-makers in a timely fashion. The gold-standard approach for monitoring nutritional situations is to conduct household surveys. However, they are costly, time consuming and do not furnish information about smaller disaggregated units. APPROACH: Brazil pioneered National Immunization Days (NIDs) in the 1980s, and later integrated them with vitamin A supplementation. This report discusses implementation of five large-scale Health and Nutrition Days (HNDs) using NIDs as a platform to monitor nutritional status and estimate coverage of health and social welfare services, including conditional cash transfer benefits. LOCAL SETING: Brazil is composed of 26 states, one federal district and 5564 municipalities, with around 18 million children under five years of age. It was decided that HNDs would be carried out among high-risk populations: children from the semi-arid north-eastern region; agrarian reform settlements; isolated rural black communities or quilombolas and municipalities of Amazonas state. RELEVANT CHANGES: It was possible to draw inferences for almost 3 million children from different subgroups of underprivileged populations who had never before been studied in such detail, including state-level data. LESSONS LEARNED: Implementation of large scale HNDs in conjunction with NIDs proved to be feasible in Brazil and resulted in data which are very relevant for policy-makers, obtained over a short period of time and at reasonably low cost. It is sensible to conclude that the experience reported here could be reproduced wherever NID coverage is very high.